Assessment of Bed Hydraulics and Metal Loadings in a Passive Vertical Flow Bioreactor in Commerce, Oklahoma. Issue 3 (11th May 2019) - Cremeans, M.M.; Devlin, J.F.; Osorno, T.C.; Nairn, R.W.
Abstract: A treatment pond, with an engineered bed that served as a passive vertical flow bioreactor (VFBR), was operated as part of a passive sequenced treatment system for the removal of metals from groundwater at the Mayer Ranch in Commerce, Oklahoma. The groundwater was contaminated by mining activities in west Commerce and discharges at this location occurred as artesian springs through improperly abandoned, over‐drilled, and cased legacy boreholes. The VFBR operated by establishing reducing conditions in the organic bed of a pond to promote metal sorption and precipitation as sulfides. In order to verify that operations were unhindered by nonuniform flow in the VFBR, an assessment of the flow uniformity in the pond was undertaken using the streambed point velocity probe (SBPVP). The velocity data were independently validated with a water balance. The outflow calculated from the SBPVP data came within 30% of the value suggested by measured inflow rates to the pond, supporting the conclusion that the SBPVP measurements were representative of flow in the VFBR, and that flow through the bed was occurring with a satisfactory level of uniformity. Water flow rates through the reactive bed were found to be up to an order of magnitude greater than those employed in the prior column testing, contributing to metal loading rates (of Cd, Pb, Zn, Ni) estimated to be two orders of magnitude greater than those tested in the columns (4.2 × 10 4 and 3.2 × 10 2  mg/m 3 /d, respectively). However, apparently rapid chemical reactions that likely occurred close to the pond water‐sediment interface contributed to the treatment system achieving its design objectives.